Fluid flow measurement a practical guide to accurate flow measurement - Upp, E. L., 1927-; LaNasa, Paul J., 1941- (Boston : Gulf Professional Pub., 2002)
There is a tendency to make flow measurement a highly theoretical and technical subject but what most influences quality measurement is the practical application of meters, metering principles, and metering equipment and the use of quality equipment that can continue to function through the years with proper maintenance have the most influence in obtaining quality measurement. This guide provides a review of basic laws and principles, an overview of physical characteristics and behavior of gases and liquids, and a look at the dynamics of flow. The authors examine applications of specific met.
Introduction -- Basic flow measurement laws -- Types of fluid flow measurement -- Basic reference standards -- From theory to practice -- Fluids -- Flow -- Operations -- Maintenance of meter equipment -- Measurement and meters -- Differential (head) meters -- Linear and special meters -- Readouts and related devices -- Proving systems -- "Loss and unaccounted for" fluids -- Auditing.
Includes bibliographical references and index.
Keywords: Fluid dynamic measurements; Flow meters; Electronic books